2012
DOI: 10.12697/poa.2012.21.06
|View full text |Cite
|
Sign up to set email alerts
|

Stress and muscle damage monitoring in high-level basketball players

Abstract: Close complex monitoring during the entire training period is essential for professional athletes to assess the effect of the training programme and to determine the quality of recovery. Follow-up of biochemical and hormonal variables throughout the season can help realize the abovementioned goals.Objectives: To determine baseline blood creatine kinase (CK) and cortisol (C) levels in professional basketball players before the beginning of regular training and to follow up the subsequent levels of blood C and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…There is lack of data regarding the dynamics of renal function in basketball. As shown in our previous research, intense training and frequent matches were associated with prolonged stress and muscle damage in basketball players [8]. We suggested that a long competitive season involving frequent matches and intense training could influence renal function, as a consequence of applying repeated physical loads, through chronically stimulating CK activity.…”
Section: Introductionsupporting
confidence: 61%
“…There is lack of data regarding the dynamics of renal function in basketball. As shown in our previous research, intense training and frequent matches were associated with prolonged stress and muscle damage in basketball players [8]. We suggested that a long competitive season involving frequent matches and intense training could influence renal function, as a consequence of applying repeated physical loads, through chronically stimulating CK activity.…”
Section: Introductionsupporting
confidence: 61%
“…9 One study suggests that monitoring the heart rate of players during practice is related to VO2max and could help to enhance the quality of practice in establishing and maintaining a level of aerobic fitness. 10 The relatively high level of aerobic demand, despite the high percent of playing time spent walking and standing, suggests aerobic metabolism is critical in the removal of lactate and the restoration of PCr, which are known to be oxygen-dependent processes 11 . The regeneration of PCr provides the muscle with energy to continue high-intensity contractions.…”
Section: Introductionmentioning
confidence: 99%
“…For thorough evaluation of team members' fitness, informative criteria need to be employed. Scientific criteria can be used to establish fitness and the quality of the game for both healthy and deaf basketball players (Gocentas, Landor, & Andziulis, 2004;Laplaud, Hug, & Menier, 2004). Existing scientific data on deaf basketball players' preparation (Milašius et al, 2007;Šatas & Milašius, 2008 a, b;Šatas, Milašius, & Dadelienė, 2005, 2010Šatas & Radžiukynas, 2003) has not yet covered analysis of players' body and functional capacity, nor change in their game activity.…”
mentioning
confidence: 99%